Narasi Ekspositoris dalam Penulisan Naskah Video Feature “Tangan Kecil, Pena Besar” - Annisa Wulandari; Kokom Komariah; Gumgum Gumilar (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The video feature "Tangan Kecil, Pena Besar" is a final project that addresses the issue of street children's education in Bandung City. In the production process, the author serves as the scriptwriter responsible for conveying messages to the audience by applying expository narrative in the scriptwriting. The purpose of this report is to explain the application of expository narrative scriptwriting in the stages of the introduction, conflict development, and resolution, which illustrates the resolution of the conflicts that have been built. The methods applied in the creation process include pre-production, production, and post-production. The results indicate that expository narrative is effective in conveying information and building audience understanding of the issues raised. In conclusion, in the video feature "Tangan Kecil, Pena Besar," the application of expository narrative in scriptwriting is crucial for delivering messages systematically and informatively, thereby increasing public awareness of the issue of street children's education.